The distributional impact of taxes and transfers : evidence from eight low- and middle-income countries - Inchauste, Gabriela; Lustig, Nora (Directions in development (Washington, D.C.). Poverty., 2017)
The World Bank has partnered with the Commitment to Equity Institute at Tulane University to implement their diagnostic tool, the Commitment to Equity (CEQ) Assessment, designed to assess how taxation and public expenditures affect income inequality, poverty, and different economic groups. The approach relies on comprehensive fiscal incidence analysis, which measures the contribution of each individual intervention to poverty and inequality reduction as well as the combined impact of taxes and social spending. The CEQ Assessment provide an evidence base upon which alternative reform options can be analyzed. The use of a common methodology makes the results comparable across countries. This volume presents eight country studies that examine the distributional effects of individual programs and policy measures, and the net effect of each country's mix of policies and programs. These case studies were produced in the context of Bank policy dialogue and have since been used to propose alternative reform options.